HISTORY OF ENVIRONMENTAL MOVEMENTS IN INDIA: A JOURNEY TOWARDS SUSTAINABILITY - Fouzdar, Sunita (International Journal of Research -GRANTHAALAYAH, 2021)
India’s environmental history reflects the long-standing relationship between people and nature, shaped by colonial policies, post-independence development models, and local resistance. Environmental movements in India emerged as historical responses to ecological degradation, social injustice, and the alienation of communities from their natural resources. Focusing on major forest, anti-dam, and biodiversity-related movements, this paper explores how these historical struggles redefined development, emphasized sustainability, and led to critical environmental reforms. These movements are more than ecological protests—they are part of a broader historical narrative of resistance, resilience, and reclaiming ecological sovereignty.